2017
DOI: 10.9790/3013-0701012833
|View full text |Cite
|
Sign up to set email alerts
|

Functional group analysis of Moringa concanensis Nimmo (Moringaceae) by FTIR spectrum

Abstract: Abstract:-In the present study deals with the FTIR profile and identify the functional components of methanol extracts of different parts of the (leaf, flower and seed) of Moringa concanensis Nimmo. The FTIR analysis was performed on a Thermo scientific spectrometer SMART iTR basic in NICOLET iS10 model using with ZnSe (zinc selenium) semiconductor the extracted plant samples of M. concanensis were scanned at room temperature within a spectral range of 4000-400 cm-1 . The vibrational assignments, intensities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Finally, the presence of a peak at 3745 cm -1 and 3845 cm -1 can be assigned to -N-H stretching. According to the study of [8,36], the presence of this band confirms the presence of amines, amides, and alcohols which again implies the presence of crude protein structure in the banana stem. Finally, there is also a peak from 600 to 750 cm -1 ; this is due to the existence of cis-disubstituted alkene.…”
Section: Ftir Analysis Results Of Banana Stem Coagulantmentioning
confidence: 73%
See 1 more Smart Citation
“…Finally, the presence of a peak at 3745 cm -1 and 3845 cm -1 can be assigned to -N-H stretching. According to the study of [8,36], the presence of this band confirms the presence of amines, amides, and alcohols which again implies the presence of crude protein structure in the banana stem. Finally, there is also a peak from 600 to 750 cm -1 ; this is due to the existence of cis-disubstituted alkene.…”
Section: Ftir Analysis Results Of Banana Stem Coagulantmentioning
confidence: 73%
“…In Figure 2, the peak between 1000 and 1300 cm -1 was assigned to -C=O-, and according to the study of Santhi and Sengottuvel [36], this is due to the existence of stretching vibrations in the amines, alcohols, and ester groups. Again, another strong peak was observed in the range of wavelength from 1600 to 1750 cm -1 , and this indicates the presence of -COOH-and -COO-.…”
Section: Ftir Analysis Results Of Banana Stem Coagulantmentioning
confidence: 87%
“…A weak absorption near 782 cm –1 indicated that the C–H bend shows alkanes. Similarly, Santhi and Sengottuvel also reported a band at 684.08 cm –1 , indicating the C–H bends show alkanes. The results of the FT-IR analysis were in good agreement with the results of the LC-ESI-QTOF-MS/MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra analysis is essential to determine various surface function of Moringa oleifera bark( MOB), as shown in Figure 2. The FTIR spectrum of MOB shown broad peaks at 3371 cm -1 cm-1 which are attributed to the O-H stretching band of hydroxyl group of phenols and alcohols in lignin and cellulose of MOB before adsorption process [38,39]. The distinct peaks observed in 3183 cm -1 are detected to the C-H stretching vibrations of aliphatic hydrocarbons [40].…”
Section: ) Surface Functional Groupsmentioning
confidence: 99%